Human dignity and euthanasia - Rueda Romero, Paulino (2021)
This article is aimed at those interested in the field of bioethics and law, and that modern life presents many challenges. Scientific and technological advances are increasing rapidly and affect our lifestyle, our knowledge and potential as human beings. In this direction, the moral, political organization and the various positions of human groups and societies, could halt the advance of science, but science is humanized, it may be necessary to reform the legal regulations and rethink the ethical principles we approach the scientific knowledge. Euthanasia is not a new phenomenon, has always reflected and is an important theme in the life of peoples. People suffering from terminal illnesses, scientists from the natural sciences give them as lost, non-life recover in a short time. Human wisdom with new technologies, new product knowledge and study efforts brainy demonstration and fortified positions appears. The struggle for life is a constant of every human being, But, when it becomes aware of irreversible cases, we started thinking about life itself. Can you use science to reinforce or transform the legal regulations and in turn, the legal regulations, can help to effectively extend scientific knowledge, rather than hinder it? Issues of this nature addresses precisely the new field of legal philosophy today.